2008
DOI: 10.1021/jm701496h
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Discovery of Anti-Inflammatory Thiazolidinones with Dual Cyclooxygenase/Lipoxygenase Inhibition

Abstract: New anti-inflammatory agents possessing dual cyclooxygenase/lipoxygenase (COX/LOX) inhibition were discovered by computer-aided prediction of biological activity for 573 virtually designed chemical compounds. Prediction of biological activity was performed by PASS, and prediction results were analyzed with PharmaExpert software. Nine 2-(thiazole-2-ylamino)-5-phenylidene-4-thiazolidinone derivatives differing by the phenyl group substitution were selected for synthesis and experimental testing as potential COX/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(95 citation statements)
references
References 32 publications
1
94
0
Order By: Relevance
“…The prostanoid product is quantified via enzyme immunoassay using a broadly specific antibody that binds to all the major prostaglandin compounds. 5,9 The inhibitory activity of the compounds was tested at arachidonic acid concentration of 1 μΜ. The compounds were added at the reaction mixture at a final concentration of 200 μΜ for a first screening of inhibitory action.…”
Section: Biological Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The prostanoid product is quantified via enzyme immunoassay using a broadly specific antibody that binds to all the major prostaglandin compounds. 5,9 The inhibitory activity of the compounds was tested at arachidonic acid concentration of 1 μΜ. The compounds were added at the reaction mixture at a final concentration of 200 μΜ for a first screening of inhibitory action.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Thus, many researchers focused on the development of dual acting COX/LOX inhibitors. 1,2,5 It has been stated that a balanced modulation of several targets can provide superior therapeutic effects and a favorable side effect profile compared to the action of a selective ligand, particularly in cases of complex diseases. 6 Licofelone, a COX-2/5-LOX inhibitor, has been evaluated in a phase III clinical trial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also useful as anti-allergic 13 , anti-inflammatory 14 and anthelmintic 15 agents and as appetite depressants 16 , intermediates for dyes 17 , plant protectants 18 , histamine H2antagonists 19 and photographic sensitizers 20 . On the other hand, careful literature survey revealed that thiazole, thiophene and pyrazole ring systems have occupied a unique position in the design and synthesis of novel biological active agents with remarkable analgesic and antiinflammatory activities [21][22][23] , in addition to their well documented potential antimicrobial activities [24][25][26][27] . Morever, thiazoles have found application in drug development for the treatment of hypertension 28 , schizophrenia 29 , HIV infections 30 , and as new inhibitors of bacterial DNA gyrase B 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Their different biological activities were reported [1,2]. Among the most important biological and pharmacological activities of both heterocyclic pharmacophoric moieties are: antihyperglycemic [3,4], antibacterial [5][6][7][8][9], antifungal [10,11], antiinflammatory [12][13][14][15][16][17], cyclooxygenase and lipoxygenase inhibitors [18,19], anticonvulsants [20,21], antitumor [22], antioxidant [23] and several other activities [1,2].…”
Section: Introductionmentioning
confidence: 99%